Isolasi, Karakterisasi, dan Produksi Inokulan Jamur Merang (Volvariella volvaceae bull. Ex. Fr) sing dari Beberapa Lokasi Budidaya di Karawang - Ani Lestari (Jurnal Agrotek Indonesia (Indonesian Journal of Agrotech), 2017)
Karawang have been some of area become center of edible mashroom production, the problem in the production of mushroom is the farmers can’t to preparation of mushroom inoculant. The aim of this research is to get the best inoculant of edible mushroom whom use for spawn from Karawang. This research conducted by explorative design used four kind of edible mushroom source; Cilamaya, Purwasari, Lamaran and Pacing. Edible mushroom isolation doing by dilution methode until 10-7 by Saraswati (2008). Constanted purity of isolat from macro and microskopist analize in PDA media by place count. The last phase in this reaserchis to get the best spawn of edible mushroom based on direction radial growht rate and interaction betweet all kind of edible mushroom. The best kind of edible musroom inoculated to grain carrier. The result showed that the best radial direction growth rate is edible mushroom from Cilamaya (64,17 mm) compre with Lamaran (61,18 mm), Purwasari (57,82) and the lower is Pacing (43,31). The same result in colony area as long as interaction growth test, edible mushroom from Cilamaya give the best performance compare with the other. Edible mushroom from Cilamaya is the best based on growt rate colony radial test and interaction in PDA media with other all of kind.Keywords: Edible mushroom, isolation, characterization, Karawang